Antioxidant recovery from pomegranate peel waste by integrating maceration and freeze concentration technology - Samsuri, S. (De Gruyter Open Ltd, 2020)
Pomegranate peel, a by-product of pomegranate fruit is rich in antioxidants. It is being used as an animal feed or discarded to the environment, which could cause an environmental problem. A new integrated process of maceration and freeze concentration was studied to recover the antioxidants from the pomegranate peel. The low temperature used in the freeze concentration assists in concentrating a high quality of antioxidants. The concentrated peel solution was tested for an antioxidant activity via 2, 2 diphenyl-1-picrylhydrazyl (DPPH) radical scavenging method. It was found that methanol gave the best extraction of antioxidants from pomegranate peel. The highest antioxidant recovery with DPPH radical scavenging of 96.14 was obtained at -16 Â°C of coolant temperature and 30 min of freezing time (p < 0.05). The integrated process has proven to be an effective method to recover the antioxidants from pomegranate peel and can be applied to recover other bioactive compounds. Â© 2020 Walter de Gruyter GmbH, Berlin/Boston.